The Impact of Financial Intermediation on Economic Growth: An Econometric Analysis for the Western Balkan Countries - Kilaj, Duresa; Morina, Fisnik; Berisha, Argjent (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This paper aims to study the impact of financial intermediation on the economic growth of the Western Balkan countries. For the implementation of this paper, we will use secondary data. For data collection, we will focus on the reports of the World Bank, IMF and Eurostat. In terms of literature review, we will use materials provided by various scientific works focused on the field of financial economics, conference materials, various books, etc. The analyzed period will be 10 years. Based on the empirical results obtained from this paper, we can say that credit and inflation have not affected financial intermediation on the economic growth of the Western Balkan countries during the years 2013 - 2022. While the interest rate and deposits have had a positive impact. Through the results obtained, we say that the results of this study will serve as good scientific and empirical evidence for future studies to be conducted in the field of financial economics. This paper presents real and consistent results regarding the relevant conclusions. The analyzed period (2013-2022) is a compelling period for drawing competent conclusions and recommendations.